Mechanismen der Korrosion bei ultrahochfestem Beton - Scheydt, Jennifer Christine (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung / Institut für Massivbau und Baustofftechnologie ; Materialprüfungs- und Forschungsanstalt Karlsruhe, 2013)
This thesis presents the results gained within a broad experimental programme on the long term behaviour in particular of ultra high performance concrete in corrosive environments. Within the investigations, the main mechanisms influencing the corrosion resistance of concrete were detected. Based on the findings, a physical model to predict the corrosion resistance of concrete was derived using the example of chemical attack.